Fyn Kinase-Mediated PKCδ Y311 Phosphorylation Induces Dopaminergic Degeneration in Cell Culture and Animal Models: Implications for the Identification of a New Pharmacological Target for Parkinson’s Disease - Saminathan, Hariharan; Ghosh, Anamitra; Zhang, Danhui; Song, Chunjuan; Jin, Huajun; Anantharam, Vellareddy; Kanthasamy, Arthi; Kanthasamy, Anumantha G. (Frontiers in Pharmacology, 2021)
Oxidative stress, neuroinflammation and apoptosis are some of the key etiological factors responsible for dopamin(DA)ergic degeneration during Parkinson’s disease (PD), yet the downstream molecular mechanisms underlying neurodegeneration are largely unknown. Recently, a genome-wide association study (GWAS) revealed the FYN gene to be associated with PD, suggesting that Fyn kinase could be a pharmacological target for PD. In this study, we report that Fyn-mediated PKCδ tyrosine (Y311) phosphorylation is a key event preceding its proteolytic activation in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) model of Parkinsonism. MPP+/MPTP induced Fyn kinase activation in N27 DAergic neuronal cells and the mouse substantia nigra. PKCδ-Y311 phosphorylation by activated Fyn initiates the apoptotic caspase-signaling cascade during DAergic degeneration. Pharmacological attenuation of Fyn activity protected DAergic neurons from MPP+-induced degeneration in primary mesencephalic neuronal cultures. We further employed Fyn wild-type and Fyn knockout (KO) mice to confirm whether Fyn is a valid pharmacological target of DAergic neurodegeneration. Primary mesencephalic neurons from Fyn KO mice were greatly protected from MPP+-induced DAergic cell death, neurite loss and DA reuptake loss. Furthermore, Fyn KO mice were significantly protected from MPTP-induced PKCδ-Y311 phosphorylation, behavioral deficits and nigral DAergic degeneration. This study thus unveils a mechanism by which Fyn regulates PKCδ’s pro-apoptotic function and DAergic degeneration. Pharmacological inhibitors directed at Fyn activation could prove to be a novel therapeutic target in the delay or halting of selective DAergic degeneration during PD.